African languages in a digital age : challenges and opportunities for indigenous language computing - Osborn, Donald Zhang (HSRC Press ; International Development Research Centre, 2010)
With increasing numbers of computers and penetration of the Internet around the world, localization of the technology and the content it carries into the many languages people speak is becoming an ever more important area for discussion and action. Localization, simply put, includes translation and cultural adaptation of user interfaces and software applications, as well as creation and translation of internet content in diverse languages. It is essential in making information and communication technology more accessible to the populations of the poorer countries, increasing its relevance to t.